2011
DOI: 10.1371/journal.pone.0016890
|View full text |Cite
|
Sign up to set email alerts
|

Transition between Two Regimes Describing Internal Fluctuation of DNA in a Nanochannel

Abstract: We measure the thermal fluctuation of the internal segments of a piece of DNA confined in a nanochannel about 50100 nm wide. This local thermodynamic property is key to accurate measurement of distances in genomic analysis. For DNA in 100 nm channels, we observe a critical length scale 10 m for the mean extension of internal segments, below which the de Gennes' theory describes the fluctuations with no fitting parameters, and above which the fluctuation data falls into Odijk's deflection theory regime. By anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 29 publications
5
68
1
Order By: Relevance
“…6 and similar data in the supplementary material. 31 The most likely discrepancy between our measurements and prior work 19 is the advancement in the barcoding technology; we were able to confirm the molecular weight scaling for the variance only by studying a very wide range of molecular weights with the large data set afforded by our high throughput method.…”
Section: B Comparison With Odijk's Theoriescontrasting
confidence: 56%
See 2 more Smart Citations
“…6 and similar data in the supplementary material. 31 The most likely discrepancy between our measurements and prior work 19 is the advancement in the barcoding technology; we were able to confirm the molecular weight scaling for the variance only by studying a very wide range of molecular weights with the large data set afforded by our high throughput method.…”
Section: B Comparison With Odijk's Theoriescontrasting
confidence: 56%
“…A previous experimental study 19 of barcode label distances in somewhat larger channels also indicated that the variance about the mean extension is larger than the prediction for the Odijk regime in Eq. (12).…”
Section: B Comparison With Odijk's Theoriesmentioning
confidence: 81%
See 1 more Smart Citation
“…Several competing technologies have arisen to accomplish this task: using a receding contact line and subsequent binding to the surface (molecular combing), [8][9][10] extensional flow (direct linear analysis), [11][12][13] and nanochannel confinement. [5][6][7]14,15 The genomic distance between neighboring barcodes is then determined by first locating the centers of the sequence-specific labels and then integrating the total backbone fluorescence intensity between these two locations. Nanochannels provide a particularly attractive approach to make such measurements since a confined chain fluctuates about its equilibrium extension; making multiple, statistically independent measurements of the distance reduces the sampling error.…”
Section: Introductionmentioning
confidence: 99%
“…If we consider a sequence-specific probe that emits light with wavelength k ¼ 573 nm (Ref. 14) and a completely extended DNA molecule with a rise of 0.34 nm per base pair (bp), then two probes would have to be separated by at least 843 bp if we take k/2 as an estimate of the resolution limit for diffraction limited optics. However, as we can see from simulation data in Fig.…”
Section: Introductionmentioning
confidence: 99%